Leadership in restaurants and its organizational outcomes: a systematic review (Research, Society and Development, 2022)
The service offered by restaurants is considered part of the population's lifestyle and contributes to the employability and economic growth of the countries. Leadership is an influencing variable for both positive and negative organizational outcomes. The objective of this Systematic Review was to identify the main organizational variables that leadership influences in restaurants. The authors developed specific search strategies for the PsycInfo, Pubmed, Web of Science, Scopus, Embase, Lilacs, Spell, Google Scholar, ProQuest Global, and BDLTD databases. The authors assessed the methodological quality of the included studies using MASTARI. Eighty-one studies were analyzed, 75 studies used quantitative data, and six studies used qualitative between 1996 and 2020. The leadership styles that showed the most favorable results were Transformational Leadership (20.9%), Leader-Member Exchange (14.8%), Supervisor Support (13.6%), and Servant Leadership (11.1%). The most researched organizational outcomes associated with leadership were Intention to Turnover and Turnover (31.9%), Organizational Commitment (22.2%), Work Performance ( 17.2%), and Job Satisfaction (15.8%). The most investigated variables in the surveys on leadership in restaurants were primarily focused on the led, indicating that researchers in the field still see the leader-led relationship in restaurants as the most needed work topic rather than organizational level variables.